Agency conflicts in residential mortgage securitization: What does the empirical literature tell us? - W. Scott Frame (Federal Reserve Bank of Atlanta, 2017)
The agency conflicts inherent in securitization are viewed by many as having been a key contributor to the recent financial crisis, despite the presence of various legal and economic constructs to mitigate them. A review of recent empirical research for the U.S. home mortgage market suggests that securitization itself may not have been a problem, but rather the origination and distribution of observably riskier loans. Low-documentation mortgages, for which asymmetric information problems are acute, performed especially poorly during the crisis. Securitized low-documentation mortgages performed better when included in deals where security issuers were affiliated with lenders or had significant reputational capital at stake and investors priced the risk of low-documentation loans via larger required equity tranches and/or higher security yields.
Keywords: G01; G21; G23; G28; 330; mortgages; banks; securitization; financial crisis